2014
DOI: 10.5935/1806-0013.20140021
|View full text |Cite
|
Sign up to set email alerts
|

Nursing approaches for pain diagnosis and classification of outcomes

Abstract: BACKGROUND AND OBJECTIVES: Nurses, as members of the health team, have to play their role to control pain, and are accountable for diagnostic evaluation, intervention and monitoring of treatment outcomes. This study aimed at identifying nursing students' approaches on interventions as from pain nursing diagnosis, according to taxonomy II of the North American Nursing Diagnosis Association and the association of nursing outcomes regarding interventions. METHODS: This is a transversal and quantitative study usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…This finding reflects the principles that guide pain management on these units, which includes nursing evaluation, and control and implementation of pharmacological and nonpharmacological interventions. Other authors found similar results regarding the linkages to this nursing diagnosis (Barros & Albuquerque, 2014). The outcomes Pain Control (1605) and Pain Level (2102) are proposed in the NNN linkage book .…”
Section: Discussionsupporting
confidence: 63%
“…This finding reflects the principles that guide pain management on these units, which includes nursing evaluation, and control and implementation of pharmacological and nonpharmacological interventions. Other authors found similar results regarding the linkages to this nursing diagnosis (Barros & Albuquerque, 2014). The outcomes Pain Control (1605) and Pain Level (2102) are proposed in the NNN linkage book .…”
Section: Discussionsupporting
confidence: 63%
“…In the case of children, it can be seen that the psychological and contextual aspects expressed in a pain situation are the main factors of their difficulty in understanding the origin of the pain and its intensity. 19 It is noteworthy that for children, the experience of pain is influenced by external and internal factors. 20 It is generally found that the more tense, anxious and fearful the child is, the more intense the painful sensation becomes.…”
Section: Evaluate Pain As Fifth Vital Sign;mentioning
confidence: 99%
“…The "changes in expressive behavior" in adjuvant signs to confirm the diagnosis of Nursing "acute pain" in older children. 19 It is understood, starting from this premise, that physiological indicators are aspects that may also help in the identification of pain in children, such as salivary cortisol, change in heart rate and respiratory rate (change in oxygen saturation). 19 It is explained, however, that these are considered as complementary measures for the identification of pain in children.…”
Section: Evaluate Pain As Fifth Vital Sign;mentioning
confidence: 99%
See 2 more Smart Citations